2008
DOI: 10.1091/mbc.e07-10-0998
|View full text |Cite
|
Sign up to set email alerts
|

The Role of GRASP55 in Golgi Fragmentation and Entry of Cells into Mitosis

Abstract: GRASP55 is a Golgi-associated protein, but its function at the Golgi remains unclear. Addition of full-length GRASP55, GRASP55-specific peptides, or an anti-GRASP55 antibody inhibited Golgi fragmentation by mitotic extracts in vitro, and entry of cells into mitosis. Phospho-peptide mapping of full-length GRASP55 revealed that threonine 225 and 249 were mitotically phosphorylated. Wild-type peptides containing T225 and T249 inhibited Golgi fragmentation and entry of cells into mitosis. Mutant peptides containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
86
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 37 publications
4
86
0
1
Order By: Relevance
“…An appealing mechanism for intercisternal adhesion has been proposed for the GRASP proteins based on X-ray crystallography and biochemistry that involves PSD-95, Dlg1, Zo-1 domain-dependent homo-oligomerization in trans (13-15). In recent years, with the advent of RNAi-based technologies, knock-down studies have broadly confirmed a role for GRASP proteins and Golgins in controlling Golgi morphology but have not agreed with each other on many notable details, leaving the field in a somewhat confused and conflictory state (10,(15)(16)(17)(18)(19)(20). In the simpler case of Drosophila, dsRNA-mediated depletion of dGRASP results in ∼30% loss of Golgi stacks, whereas double depletion of dGRASP and dGM130 was shown to unstack the Golgi, as examined by EM (21).…”
mentioning
confidence: 99%
“…An appealing mechanism for intercisternal adhesion has been proposed for the GRASP proteins based on X-ray crystallography and biochemistry that involves PSD-95, Dlg1, Zo-1 domain-dependent homo-oligomerization in trans (13-15). In recent years, with the advent of RNAi-based technologies, knock-down studies have broadly confirmed a role for GRASP proteins and Golgins in controlling Golgi morphology but have not agreed with each other on many notable details, leaving the field in a somewhat confused and conflictory state (10,(15)(16)(17)(18)(19)(20). In the simpler case of Drosophila, dsRNA-mediated depletion of dGRASP results in ∼30% loss of Golgi stacks, whereas double depletion of dGRASP and dGM130 was shown to unstack the Golgi, as examined by EM (21).…”
mentioning
confidence: 99%
“…This activity arose as the result of the tethering functions displayed by GRASP65 and GRASP55, through their interactions with their partner proteins GM130 and golgin-45, respectively (2)(3)(4). Several other studies have shown more recently that the GRASPs are involved in the maintenance of the structure of the Golgi ribbon in mammal cells during interphase, in controlling the fragmentation of the Golgi complex at the onset of mitosis (5)(6)(7)(8), in establishing cell polarity in migrating cells (9), and in the consumption of COPII vesicles and the formation of the cis-Golgi in yeast (10).…”
mentioning
confidence: 99%
“…Indeed, a direct role for GRASPs in cargo transport has so far been established only for the unconventional secretion routes in Dictyostilium and Drosophila (11,12), whereas they have been shown not to be directly involved in the trafficking of commonly studied reporter cargo proteins along the "conventional" secretory pathway (e.g. the temperature-sensitive (ts-045) mutant of the G protein of vesicular stomatitis virus (VSVG) 2 ) and secretory horseradish peroxidase (5,6,13,14). GRASPs can engage different types of interactions including the ones mediated by their PDZ domains, through which the GRASPs cannot only homodimerize, thus participating in cisternal stacking (15) but can also bind the C-terminal valine motifs (C-TVM) of membrane proteins such as protransforming growth factor ␣ and p24a (16,17).…”
mentioning
confidence: 99%
“…24 Phosphorylation of GRASP55 may cause lateral unlinking of stacks, 22 while others could not confirm this observation. 25 Therefore, the molecular mechanisms that organize lateral unlinking remain unclear. However, inhibition of this step prevents cells from entering mitosis, suggesting the activation of a Golgi-specific checkpoint that arrests cells in G 2 .…”
Section: Disassembly Of the Golgi During Mitosismentioning
confidence: 99%
“…However, inhibition of this step prevents cells from entering mitosis, suggesting the activation of a Golgi-specific checkpoint that arrests cells in G 2 . 22,25,26 The observation that the Golgi can still be divided during mitosis even if the cisternae remain stacked, suggests that the potential checkpoint is acting at an early stage when stacks are still intact. 27,28 During prophase and metaphase, the cisternae of the unlinked stacks are then converted into a collection of tubular and vesicular structures by COPI-dependent and COPI-independent mechanisms.…”
Section: Disassembly Of the Golgi During Mitosismentioning
confidence: 99%